IMPLEMENTATION OF ISLAMIC GUIDANCE & COUNSELING OF ENFORCING THE DISCIPLINE STUDENTS IN MTS. AL WASHLIYAH GADING TANJUNGBALAI - Aida Nasma (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The problem in this research is the implementation of Islamic guidance &counseling in upholding student discipline in MTs. Al Washliyah Gading Tanjungbalai. This study aims to establish the condition of studenttraining, the application of Islamic advice conducted by guidance & counseling teachers, the implementation of Islamic guidance &counseling in raising student discipline in MTs. Al Washliyah Gading Tanjungbalai. This research is phenomenological in a qualitative approach.The collecting dataused observation, interview, and documentation. In analyzing the data, the researcher used qualitative analysis with steps of data exposure, data reduction, and conclusion description. The results of this study are: (1) the condition of the student discipline is quite good (2) the implementation of Islamic guidance & counseling conducted by teachers in optimally (3) the application of Islamic guidance & advice in upholding student discipline ineffectively.